Polymeric nanomedicine for overcoming resistance mechanisms in hedgehog and Myc-amplified medulloblastoma. (November 2021) - Kumar, Virender; Wang, Qiyue; Sethi, Bharti; Lin, Feng; Kumar, Vinod; Coulter, Donald W.; Dong, Yuxiang; Mahato, Ram I.
Abstract: Chemoresistance and inadequate therapeutics transport across the blood brain barrier (BBB) remain the major barriers to treating medulloblastoma (MB). Hedgehog (Hh) and IGF/PI3K pathways regulate tumor cell proliferation and resistance in MB. Current Hh inhibitors are effective initially to treat SHH-MB but acquire resistance. Herein, we showed that Hh inhibitor MDB5 and BRD4/PI3K dual inhibitor SF2523 synergistically inhibited the proliferation of DAOY and HD-MB03 cells when used in combination. Treatment of these MB cells with the combination of MDB5 and SF2523 significantly decreased colony formation and expression of MYCN, p-AKT, and cyclin D1 but significantly increased in Bax expression, compared to individual drugs. We used our previously reported copolymer mPEG-b-PCC-g-DC copolymer, which showed 8.7 ± 1.0 and 6.5 ± 0.1% loading for MDB5 and SF2523 when formulated into nanoparticles (NPs). There was sustained drug release from NPs, wherein 100% of MDB5 was released in 50 h, but only 60% of SF2523 was released in 80 h. Targeted NPs prepared by mixing 30:70 ratio of COG-133-PEG-b-PBC and mPEG-b-PCC-g-DC copolymer delivered a significantly higher drug concentration in the cerebellum at 6 and 24h after intravenous injection into orthotopic SHH-MB tumor-bearing NSG mice. Moreover, systemic administration of COG-133-NPs loaded with MDB5 and SF2523 resulted in decreased tumor burden compared to non-targeted drug-loaded NPs, without any hepatic toxicity. In conclusion, our nanomedicine of MDB5 and SF2523 offers a novel therapeutic strategy to treat chemoresistant MB.